Menyelami Dunia Sastra Digital: Studi Kasus Dilan 1990 dalam Konteks Literasi Digital - Munthe, Dristyana; Julaeha, Ai Siti; Pangestuti, Peni; Sicilia R, Nova (Program Studi Magister Linguistik Terapan UNJ, 2023)
In the era of Society 5.0, technological advancements play a significant role in various aspects of life, including the transformation of literature. Literary works that were once only available in print format can now be accessed digitally through virtual spaces. One notable phenomenon in digital literature is the novel Dilan 1990. This study aims to describe the characteristics of this literary work and the digital aspects surrounding it. The research employs a qualitative approach with a case study design. The case study method was chosen to analyze the phenomenon of digital literature as represented by the novel Dilan 1990, in the context of digital literacy and reader interaction patterns through social media. The findings reveal that social media and digital platforms have influenced how readers interact with the novel. Content dissemination via social media has broadened its readership, while active reader engagement in creating derivative works—such as fan art and fan fiction—has contributed to the expansion of the story’s narrative universe. These findings indicate that Dilan 1990 serves as a representation of literary transformation in the digital age and highlights the potential of digital literacy in enriching the reader’s experience.